(untitled) (Linguostylistic Studies, 2014)
The article defines the place, role and the importance of Lesya Ukrainka poetry in the development of the Ukrainian literary language. The main artistic lingvo-stylestemes (linguistic units with stylistic meaning) of poet’s speech are described in the article as well. Lesya Ukrainka was a brilliant stylist in several dimensions: as a poet, an essayist, a critic, a playwright. In the linguistic discussions of the late XIX – the early XX centuries, being a spiritual pupil of Mikhail Dragomanov and a contemporary of Ivan Franko and Hrushevsky, she supported and developed the new philosophy of the Ukrainian literary language: to remove taboos and restrictions in the Ukrainian language and to expand the functional field of the Ukrainian language. Moreover, her aim was not only to admire the beauty of the national language, but build the cultural language, create the norms of standard language using the achievements of all major dialects, forming journalistic and scientific styles to develop education and the culture of work of the Ukrainian people in their native language. Enriching the development of the literary Ukrainian language, Lesya Ukrainka created and improved new poetic forms of speech, polished them, adding popular folklore and colloquial vocabulary to them. She also spread semantic boundaries of contextual meanings of words, and was the first who perfected the style of the genre forms (especially new ones) she introduced to the literary language. Key words: poetry, lingvo-stylesteme (linguistic units with stylistic meaning), speech, word, idea, thought, song. References